Management of Zakat Infak and Shadaqah in Lazismu Surakarta City - Narimo, Sabar; Romadhoni, Defri Nur (Universitas Muhammadiyah Surakarta, 2022)
This study aims to describe how the management of zakat, infaq, and shadaqah funds at LAZISMU Surakarta City, as well as to describe the supporting factors and inhibiting factors faced LAZISMU Surakarta City in carrying out its management. The type of research is qualitative with ethnographic design. Data collection techniques used in this study are observation, documentation and in-depth interviews. Where for the validity of the data, the researchers used source triangulation. The data analysis technique is descriptive analysis. The results showed that the management of zakat, infaq, and shadaqah at LAZISMU Surakarta City included the management of collection and distribution. Its management consists of planning, organizing, actuating, and controlling. The supporting factors for its management are having clear guidelines, qualified human resources in their fields, high public trust and Muhammadiyah associations, while the inhibiting factors are the density of Islamic education activities, not being able to enter large institutions or companies, as well as changing work patterns and habits in idealizing management. As a result, it is possible to conclude that LAZISMU Surakarta City has implemented a systematic and structured management system.